The prophets agree: the function of the book of the Twelve Prophets in Acts - White, Aaron W. ca. 21. Jh. (Biblical interpretation series, 2020)
Acknowledgments -- Abbreviations -- Introduction: A Case for a Study on the LXX-Twelve Prophets in Acts -- I Flourishing Bones: an Introduction to a Study of the LXX-Twelve Prophets in Acts -- I Previous Work on the TP in Acts and Models of Interpretation -- I A New Study on the TP in Acts -- V The Argument and the Direction of the Study -- 1 “I Will Pour Out My Spirit”: Jesus the Lord and the Lukan Reading of LXX-Joel 3:1–5 in Acts 2 -- The Text of LXX-Joel 3:1–5 and of Acts 2:17–21 -- I Introduction -- I “I will pour out My Spirit”: LXX-Joel 3:1–5 -- I LXX-Joel 3:1–5 in Acts 2: God’s Attestation of the Lord and His Witnesses -- V Joel 3:1–5 in The Testament of Judah 24 -- V Luke and The Testament of Judah 24: a Conversation among Readers -- 2 “Forty Years”: the Divided People of God and the Lukan Reading of LXX-Amos 5:25–27 in Acts 7:42–43 -- The Text of LXX-Amos 5:25–27 and of Acts 7:42–43 -- I Introduction -- I “Forty Years”: Amos 5:25–27 as a Look Back to the Exodus -- I Amos 5:25–27 in Acts 7:42–43 -- V Amos in the Damascus Document: CD-A 7:13–8:1 -- V Amos 5:25–27 in CD-A and Acts 7: Reading Amos 5 in Community -- 3 “I am Doing a Work”: the Gentiles as God’s People and the Lukan Reading of LXX-Habakkuk 1:5 in Acts 13 -- The Text of LXX-Habakkuk 1:5 and of Acts 13:41 -- I Introduction -- I Habakkuk: the Announcement of an Amazing Judgment -- I The Work of God: the Role of Habakkuk 1:5 in Acts 13 -- V “The Traitors in the Latter Days”: the Reading of Hab. 1:5 by 1QpHab 1.16–2.10 -- V Habakkuk 1:5 in 1QpHab and Acts 13: a Conversation among Readers -- 4 “All the Gentiles Who Are Called”: Sending the Gentiles Mission and the Lukan Reading of LXX-Amos 9:11–12 in Acts 15 -- The Text of LXX-Amos 9:11–12 and of Amos 15:16–18 -- I Introduction -- I LXX-Amos 9:11–12: a Rebuilt Davidic Reign in the Eschatological Future -- I LXX-Amos 9:11–12 in Acts 15: Gentile as Gentile -- V Amos 9:11 in 4Q Florilegium Frgs. 1–2 and 21, 1 -- V Luke and 4QFlor: a Discussion among Readers of Amos 9:11 (and 12) -- Conclusion: Reading the Greek Book-of-the-Twelve-Prophets in Acts -- I What Was This Study About? -- I Luke and His Co-readers -- I How Each Quotation Built towards One Argument -- V What If the Greek Twelve-Prophets Were Not in Acts? -- Appendix -- Selected Texts -- Works Cited --.